Primulina pingleensis (Gesneriaceae), a new species from Guangxi, China - Qin, Ying; Meng, Tao; Chen, Hai-Ling; Liu, Yan (Phytotaxa, 2022)
Primulina pingleensis, a new species from the limestone area of Guangxi, China is described and illustrated. The new species is similar to P. pseudoheterotricha and P. macrodonta, but can be easily distinguished from the latter two by its narrowly lanceolate calyx lobes, strongly laterally compressed corolla tube, deeply bilobed stigma and so on. Detailed morphological descriptions, photographs and taxonomic notes are provided here.